2009
DOI: 10.1007/s11626-009-9236-z
|View full text |Cite
|
Sign up to set email alerts
|

The proliferative effects of retinoic acid on primary cultures of adult rat type II pneumocytes depend upon cell density

Abstract: Retinoic acid (RA) is important for maintaining integrity of alveolar epithelial cells, but the mechanism has not been defined. We cultured type II pneumocytes at confluent, high cell density (10(4) cells/mm(2)) and found that RA (10(-6) M) inhibited thymidine incorporation to 60% of control, despite a dose-dependent increase in epidermal growth factor receptor (EGFR) levels. However, at lower, subconfluent density (10(2) cells/mm(2)), RA stimulated thymidine incorporation to 280% of control. EGF increased thy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 48 publications
0
9
1
Order By: Relevance
“…Together, this suggests that RA signalling does not directly regulate alveolar epithelial repair. This was surprising and contrasts with previous reports of a proliferative role of RA in rat neonatal alveolar epithelial cells,38 suggesting the role of RA signalling in juvenile and adult alveolar epithelium may be distinct. Therefore, although alveolar epithelial growth necessarily occurs during RA-induced adult lung regeneration, this may be indirect, mediated by effects of RA on other lung cell types.…”
Section: Discussioncontrasting
confidence: 99%
“…Together, this suggests that RA signalling does not directly regulate alveolar epithelial repair. This was surprising and contrasts with previous reports of a proliferative role of RA in rat neonatal alveolar epithelial cells,38 suggesting the role of RA signalling in juvenile and adult alveolar epithelium may be distinct. Therefore, although alveolar epithelial growth necessarily occurs during RA-induced adult lung regeneration, this may be indirect, mediated by effects of RA on other lung cell types.…”
Section: Discussioncontrasting
confidence: 99%
“…Retinoid X receptors can homodimerize or heterodimerize with a large variety of proteins, including retinoic acid receptors (RARs), thyroid hormone receptor (THR), the vitamin D receptor (VDR), farnesoid X receptor (NR1H4) and other nuclear receptors (NRs), as well as the family of peroxisome proliferator-activated receptors (PPARs) [40]. While retinoic acid and its receptor has been implicated in lung development and injury [41][48] the precise role of RXR remains to be clarified. Because of their many potential binding partners, the function of RXRs can be complex; certain NR heterodimers (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Our observations are consistent with these results, suggesting that higher SP-C levels induced by KGF treatment may be an intrinsic protective mechanism in pulmonary injury. Earlier studies showed that AECIIs are the progenitors of alveolar epithelial cells (16). After lung injury and AECI damage, AECIIs can proliferate and repair the epithelium.…”
Section: Discussionmentioning
confidence: 99%